Feminist Theory: A Research Agenda for HRD. Issue 3 (August 2019) - Hirudayaraj, Malar; Shields, Lauren
The Problem: Limited research representing the field of human resource development (HRD) has challenged the masculine rationality in organizational culture, processes, and discourse; questioned power or gender hegemony within organizations; or examined how oppression and hegemony are manifested in the lives of different groups of women in a variety of work contexts. This limited scope of research has resulted in a lack of consideration and application of feminist theory, a valuable framework for examining issues relating to inequity and the subjugation of women. Compared with related fields, studies applying feminist theory in HRD research are fewer in number and less robust in terms of issues explored, research design, and target groups examined. The Solution: A deeper examination of (a) populations beyond White middle class women, (b) the lives and experiences of women from varying backgrounds, (c) asymmetrical power relationships, (d) opportunities for women to gain knowledge and power, (e) the use of language and power to silence women, (f) gender as a social construct and essential category of analysis, and (g) ways to promote social change are presented along with recommendations to broaden the scope of research that applies feminist theory in HRD research and practice. The Key Stakeholders: The examination of feminist theory is expected to benefit HRD researchers, practitioners, scholars, and women in the workforce.